Evaluation on effectiveness and operation mechanism of management system for severe mental disorders: a literature study - Qin-wen YU; Pei-wu SHI; Qun-hong SHEN; al (); Institute Research; Health of; Strategies Development; University Fudan; 200032 Shanghai; China (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze operational effectiveness and mechanism of management system for severe mental disorder (SMD) prevention and control in China for providing references to subsequent policy formulation. MethodsThrough searching official websites, we retrieved policy documents relevant to management on SMDs issued by governmental departments and professional institutions as of December 31, 2018 in 31 provincial-level administrative divisions (PLADs) across mainland China and analyzed the completeness and operation mechanism of the management scheme from four perspectives: management and monitoring, planning and evaluation, financing and compensation, and coordination and motivation based on evaluation standards for effectiveness of a public health system. The indicator data on management of SMD from 2014 through 2018 were also collected from National Severe Mental Disorder Information System and research literatures. The relationships between management implementation and effectiveness were analyzed using fixed effects model. ResultsFor 31 PLADs in 2018, the average appropriate degree of SMD management scheme was 43.87%, with an increment of 22.08% to that in 2014 and a gap of 48.39% to the appropriate standard (85%). The dimensional appropriate degree of the SMD management scheme was the highest (64.96%) for financing and compensation mechanism but the lowest (23.69%) for coordination and motivation mechanism. For the dimension of management and monitoring in 2018 at national level, the completeness degree of content and form was relatively high (89.29%) but the degree of clarity for responsibility assignment was relatively low (24.91%), and the degree of management procedure feasibility was only 6.48%; for the dimension of planning and evaluation, the coverage of long-term planning was as high as 96.24%. The results of fixed effect model analysis showed that after adjusting for gross domestic product, significant increase of 1.00 % for completeness of regional SMD scheme, 1.54% for average standardized management rate, and 0.28% for average regular medication of SMD patients were observed (all P < 0.05). ConclusionThe management mechanism of severe mental disorders has been steadily improved in China from 2014 to 2018; for the management scheme, the coverage of management standards and medium and long-term planning were relatively high, but the coordination and motivation mechanism and t responsibility assignment need to be improved.